Mammals collected by Johann Jakob von Tschudi in Peru during 1838-1842 for the Muséum d’Histoire Naturelle de Neuchâtel, Switzerland - Serrano-Villavicencio, José Eduardo; Bartoletti, Tomás; Bueno, Celia (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
During his first trip to Latin America (1838-1842), the Swiss naturalist Johann Jakob von Tschudi collected a large series of Peruvian fauna, including birds, reptiles, fish, amphibians, and mammals. On this last group, Tschudi published two pioneering works, “Mammalium conspectus” and “Untersuchungen über die Fauna Peruana”, in which he described new species and presented the first systematic lists of the Peruvian fauna. Despite the relevance of Tschudi’s work, his lists of mammals have been poorly consulted in contemporary research. In order to rectify and update these lists, we reviewed all of Tschudi’s writings on mammals, situating his expedition in its global context. Additionally, we looked and reviewed the material collected by Tschudi, including types, held at the Muséum d’Histoire Naturelle de Neuchâtel (Neuchâtel, Switzerland). Of the 119 species listed by Tschudi, approximately 87 are currently recognized as valid. Furthermore, at least 21 type specimens representing 14 of the 24 species described by Tschudi are still held at Neuchâtel’s collection. We finally corrected and clarified the date of publication of Tschudi’s new species. Tschudi’s Peruvian expedition drew international recognition in his days, being a milestone in the history of scientific institutionalization in Switzerland, and remains as a relevant legacy for the study of Peruvian biodiversity
Keywords: History; Mammalogy; Scientific collections; Travels in Peru; Type material